1996
DOI: 10.1044/jshr.3903.494
|View full text |Cite
|
Sign up to set email alerts
|

Speaking Clearly for the Hard of Hearing IV: Further Studies of the Role of Speaking Rate

Abstract: The contribution of reduced speaking rate to the intelligibility of “clear” speech (Picheny, Durlach, & Braida, 1985) was evaluated by adjusting the durations of speech segments (a) via nonuniform signal time-scaling, (b) by deleting and inserting pauses, and (c) by eliciting materials from a professional speaker at a wide range of speaking rates. Key words in clearly spoken nonsense sentences were substantially more intelligible than those spoken conversationally (15 points) when presented in quiet for li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
159
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(179 citation statements)
references
References 24 publications
9
159
1
Order By: Relevance
“…The data provided strong evidence that talkers successfully maintained clear speech articulatory modifications across longer stretches of speech such that intelligibility was increased in all portions of the paragraphs. Previous clear speech research largely focused on intelligibility of isolated vowels, words, and short sentences ͑Picheny et Payton et al, 1994;Uchanski et al, 1996;Bradlow and Bent, 2002;Bradlow et al, 2003;Ferguson, 2004;Ferguson and Kewley-Port, 2002͒. The current results expand on these findings by demonstrating that clear speech modifications can increase the intelligibility of longer and more complex utterances.…”
Section: Summary and Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The data provided strong evidence that talkers successfully maintained clear speech articulatory modifications across longer stretches of speech such that intelligibility was increased in all portions of the paragraphs. Previous clear speech research largely focused on intelligibility of isolated vowels, words, and short sentences ͑Picheny et Payton et al, 1994;Uchanski et al, 1996;Bradlow and Bent, 2002;Bradlow et al, 2003;Ferguson, 2004;Ferguson and Kewley-Port, 2002͒. The current results expand on these findings by demonstrating that clear speech modifications can increase the intelligibility of longer and more complex utterances.…”
Section: Summary and Discussionsupporting
confidence: 73%
“…Previous work on English clear speech production and perception has established that naturally produced clear speech enhances intelligibility for various listener populations including adults with normal or impaired hearing ͑Picheny et Payton et al, 1994;Uchanski et al, 1996;Ferguson, 2004;Ferguson and Kewley-Port, 2002;Bradlow, 2005͒, elderly adults ͑Schum, 1996;Helfer, 1998͒, both native and non-native listeners of the target language ͑Bradlow and Bent, 2002;Bradlow and Alexander, 2007;Smiljanic and Bradlow, 2007͒, and children with and without learning impairments ͑Bradlow et al, 2003͒. Acoustic comparisons of conversational and clear speech in English have shown that clear speech modifications typically involve enhancement of the overall acoustic salience of the speech signal by means of a decreased speaking rate, longer and more frequent pauses, an expanded pitch range, greater sound pressure levels, more salient stop releases, greater obstruent intensity, increased energy in the 1000-3000 Hz range of long-term spectra, and increased modulation depth of low frequency modulations of the intensity envelope ͑Picheny et Bradlow et al, 2003;Liu et al, 2004;Krause and Braida, 2004;Smiljanic and Bradlow, 2005͒.…”
Section: Introductionmentioning
confidence: 99%
“…Rate variability within a given speaker is not achieved by a constant "stretching" or "shrinking" of the acoustic waveform in the temporal domain. Rather, certain acoustic segments are more dramatically reduced in duration than others when overall speaking rate is increased, and various other acoustic/phonetic changes (e.g., vowel reduction) occur in response to changes in speaking rate (see, e.g., Klatt, 1973Klatt, , 1976Lehiste, 1972;Picheny, Durlach, & Braida, 1986Port, 1981;Uchanski, Choi, Braida, Reed, & Durlach, 1996). Thus, an increase or decrease in speaking rate is clearly a dynamic, multidimensional transformation of the speech signal.…”
Section: Discussionmentioning
confidence: 99%
“…Acoustic comparisons of conversational and clear speech in English have shown that clear speech modifications typically involve enhancement of the overall acoustic salience of the speech signal by means of a decreased speaking rate, longer and more frequent pauses, an expanded pitch range, greater sound pressure levels, more salient stop releases, greater obstruent intensity, increased energy in the 1000-3000 Hz range of long-term spectra, and increased modulation depth of low frequency modulations of the intensity envelope [3,12,14,18,19,26,28].…”
Section: Introductionmentioning
confidence: 99%